FRAMING ANALYSIS IN KOREAN DRAMA "BUSINESS PROPOSAL" ON VIEWERS' PERCEPTION OF SOCIAL DISPARITIES AMONG GEN Z - Maretza, Trize; Putri, Valentina Rahmania; Razzaq, Abdur; Nugraha, Muhamad Yudistira (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT The popular Korean drama "Business Proposal" tells the story of romance and work, but also subtly highlights the social gaps that are seen in the characters, This study aims to analyze the framing used in this drama to understand how social gaps are portrayed and how they affect viewers' perceptions. The research method used is quantitative, through content analysis of dramas and surveys to viewers. Content analysis shows that the drama "Business Proposal" utilizes framing that tends to reinforce stereotypes of social inequality, such as social class differences, lifestyles, and educational access. This framing is reflected in the differences in characters, storylines, and dialogue. For example, the main character who comes from a wealthy family has a luxurious lifestyle and high education, while the character who comes from a poor background is able to face difficulties in achieving his goals. Surveys of viewers revealed that the framing used in dramas has an influence on their perceptions. Most respondents felt that the drama "Business Proposal" did not provide a concrete solution to the problem of social inequality and tended to reinforce stereotypical views. This research provides important implications for the Korean film industry to present stories about social inequality with a more balanced and realistic perspective. It is hoped that the media in the future can display a more objective and inclusive representation of social inequality, thereby encouraging constructive discussion and reflection in society.   ABSTRAK Drama Korea populer "Business Proposal" menceritakan kisah percintaan dan pekerjaan, tetapi juga secara halus menyoroti kesenjangan sosial yang terlihat pada para tokohnya. Penelitian ini bertujuan untuk menganalisis framing yang digunakan dalam drama ini untuk memahami bagaimana kesenjangan sosial digambarkan dan bagaimana kesenjangan tersebut memengaruhi persepsi pemirsa. Metode penelitian yang digunakan adalah kuantitatif, melalui analisis konten drama dan survei kepada pemirsa. Analisis konten menunjukkan bahwa drama "Business Proposal" memanfaatkan framing yang cenderung memperkuat stereotip ketimpangan sosial, seperti perbedaan kelas sosial, gaya hidup, dan akses pendidikan. Framing ini tercermin dalam perbedaan karakter, alur cerita, dan dialog. Misalnya, tokoh utama yang berasal dari keluarga kaya memiliki gaya hidup mewah dan pendidikan tinggi, sedangkan tokoh yang berasal dari latar belakang miskin mampu menghadapi kesulitan dalam mencapai tujuannya. Survei kepada pemirsa mengungkapkan bahwa framing yang digunakan dalam drama memiliki pengaruh terhadap persepsi mereka. Sebagian besar responden merasa bahwa drama "Business Proposal" tidak memberikan solusi konkret terhadap masalah ketimpangan sosial dan cenderung memperkuat pandangan stereotip. Penelitian ini memberikan implikasi penting bagi industri film Korea untuk menyajikan cerita tentang ketimpangan sosial dengan perspektif yang lebih berimbang dan realistis. Diharapkan media di masa mendatang dapat menampilkan representasi ketimpangan sosial yang lebih objektif dan inklusif, sehingga mendorong diskusi dan refleksi yang konstruktif di masyarakat.